POTENSI DAN PELUANG PENGEMBANGAN KERAJINAN COR KUNINGAN SUNGAI PUAR DALAM ERA REVOLUSI INDUSTRI 4.0 - Riswel Zam; Ferawati Ferawati (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2020)
Brass cast craft in Sungai Puar has existed since ancient times with its ebb and  flow of existence caused by various internal and external factors. This paper discusses the potential and opportunities for development of this brass cast craft in the 4.0 Industrial Revolution Era, an era that focuses on the use of the latest technology which covering all aspects of its production and marketing activities. The lack of interest of younger generation as the successors of this activity is a concern for the existence of this brass cast craft.  On the other hand, the long duration of time in the production system, the availability of raw materials, as well as the marketing of product are problems faced by craftsmen and business owners. The application of the concepts contained in this revolution and the support of stakeholders are expected to overcome these problems.  Thus the brass cast craft of Sungai Puar is able to develop again with all its associated elements that become its supporters such as design, nature, and culture of Sungai Puar through various activities.  ABSTRAK Kerajinan cor kuningan di Sungai Puar sudah ada sejak zaman dahulu dengan pasang surut keberadaannya yang disebabkan oleh berbagai faktor internal dan eksternal.  Tulisan ini membahas potensi dan peluang pengembangan kerajinan cor kuningan ini dalam era Revolusi Industri 4.0, sebuah era yang berfokus pada penggunaan teknologi terkini mencakup seluruh aspek dalam kegiatan produksi maupun pemasarannya.  Kurangnya minat generasi muda sebagai penerus kegiatan ini menjadi kecemasan terhadap keberadaan kerajinan cor kuningan ini.  Di samping itu panjangnya durasi waktu dalam sistem produksi, ketersediaan bahan baku, serta pemasaran produk menjadi persoalan yang dihadapi perajin dan pemilik usaha.  Penerapan konsep yang terkandung dalam revolusi industri ini, serta dukungan dari stakeholders diharapkan permasalahan tersebut dapat diatasi.  Dengan demikian kerajinan cor kuningan Sungai Puar kembali berkembang dengan segala unsur yang terkait dan menjadi pendukungnya seperti desain, serta alam dan budaya Sungai Puar melalui berbagai kegiatan.